Human leukocyte antigen-A*33:03-B*58:01-DRB1*15:140, a deduced probable human leukocyte antigen haplotype in association with a human leukocyte antigen low-incidence allele DRB1*15:140 in Taiwanese individuals: A case analysis - Kuo-Liang Yang; Zheng-Zhong Zheng (Tzu Chi Medical Journal)
Objective: Human leukocyte antigen (HLA)-DRB1*15:140 is a low-frequency allele in the HLA-DRB1 locus. The aim of this study is to confirm the ethnicity of DRB1*15:140 and to deduce a probable HLA-DRB1*15:140-associated HLA haplotype in Taiwanese individuals. Materials and Methods: A total of 1815 healthy unrelated Taiwanese individuals and 14,562 unrelated mainland Chinese individuals were tested for HLA using a sequence-based typing method. Polymerase chain reaction was performed to amplify exons 2 and 3 of the HLA-A and HLA-B loci and exons 1 and 2 of the HLA-DRB1 locus using group-specific primer sets. The amplicons were sequenced in both directions with the BigDye Terminator Cycle Sequencing Ready Reaction Kit according to the manufacturer's protocols. Results: The DNA sequence of HLA-DRB1*15:140 is identical to DRB1*15:02:01:01 in exons 1 and 2, except at residue 91 of DRB1*15:02:01:01 where a G in DRB1*15:02:01:01 is replaced by an A in DRB1*15:140 (codon 2; GAC->AAC). The nucleotide substitution in exon 1 introduces a one amino acid substitution at residue 2 where an aspartic acid (D) in DRB1*15:02:01:01 is replaced by an asparagine (N) in DRB1*15:140. We deduced the probable HLA haplotype associated with DRB1*15:140 in Taiwanese to be HLA-A*33:03-B*58:01-DRB1*15:140. Conclusion: Information on the ethnicity and distribution of DRB1*15:140 and its deduced probable HLA haplotype in association with the low-incidence allele is of value for HLA-testing laboratories for reference purposes and can help bone marrow donor registries find compatible donors for patients with this uncommon HLA allele.